Ion-molecule reactions involving methyl isocyanide and methyl cyanide - N. Dechamps; R. Flammang; M. Boulvin; L. Lamote; P. Gerbaux; V. T. Ngan; M. T. Nguyen (My University, 2007)
Ion-molecule reactions involving methyl isocyanide and methyl cyanide
Keywords: Ion-molecule reactions